Correction: Untangling population structure and genetic diversity of reticulocyte binding protein 2b (PvRBP2b) erythrocytic stage vaccine candidate in worldwide Plasmodium vivax isolates - Nourani, Leila; Mehrizi, Akram Abouie; Zakeri, Sedigheh; Djadid, Navid Dinparast (PLOS ONE, 2024)
null